Surface water availability and groundwater in River Fish basin - Itabira-MG (Research, Society and Development, 2019)
The Knowledge of aquifer regulatory capacity on the natural discharge of rivers, even on a regional scale, provides subsidies that help in the knowledge of the quantitative correlation between surface water and groundwater. This research is quantitative in nature and is specifically a case study. The objective of this work is to evaluate and quantify the relationship between surface and groundwater from hydrograph analyzes of the total flow in the river fish basin. Itabira city is located in the river fish basin and located in the country's largest mining center, presents numerous problems of water supply. From the fluviometric data of five spillways, it was possible to quantify the surface and underground components using the Barnes method through hydrographs of the total flow of the Peixe river basin. The percentage of subterranean deforestation related to the total deforestation showed values higher than 60%. The springs and wells drilled in the Cauê Aquifer, present the highest flows, followed by the wells drilled in the Piracicaba Group. The base flow does not present intermittence, it is assumed that the aquifers maintain the flow of the rivers even in drier periods, and there is a correlation between the geological, geomorphological and hydrological and hydrogeological conditions.